Mathematics Stack Exchange is a question and answer site for people studying math at any level and professionals in related fields. Join them; it only takes a minute:

Sign up
Here's how it works:
  1. Anybody can ask a question
  2. Anybody can answer
  3. The best answers are voted up and rise to the top

I'm having difficulty with the following problem. Any help would be appreciated.

Problem: Consider the sequence spaces $l_p$ with the usual norm. If $1\le p\le q\le \infty$, I want to show the following inequality for any sequence $a$.

$$\|a\|_q\le \|a\|_p$$

If we restrict to $\mathbb{R}^n$ but still use the $l_p$ norms, I also want to show this: $$\|a\|_q\le \|a\|_p\le n^{\frac{1}{p}-\frac{1}{q}}\|a\|_q$$

Work so far: I strongly suspect that a clever application of Hölder is needed here, but I tried the following for the first inequality:

First, we consider the case where a finite number of elements in the sequence are nonzero. We want to prove

$$||x||_q\le ||x||_p \Leftrightarrow \left(\sum_1^n |x_j|^q\right)^{\frac{1}{q}} \le \left(\sum_1^n |x_j|^p\right)^{\frac{1}{p}}.$$

We induct on $n$. The base case is clear. Because we can multiply all of the variables by a constant without affecting the inequality, we assume $x_n=1$. Assume we have proven the inequality for $n-1$. Then

$$\left(\sum_1^{n-1} |x_j|^q\right) \le \left(\sum_1^{n-1} |x_j|^p\right)^{\frac{q}{p}}$$

It suffices to show that

$$\left(\sum_1^{n-1} |x_j|^q\right) + 1 \le \left(\sum_1^{n-1} |x_j|^p+1\right)^{\frac{q}{p}}$$

This is equivalent to

$$\left(\sum_1^{n-1} |x_j|^q\right)\le \left(\sum_1^{n-1} |x_j|^p+1\right)^{\frac{q}{p}}-1$$

So we need to show that if $f(x)=x^{q/p}$, then $f(x+1)\ge f(x)+1$. But this is clear, as $q\ge p$. Now I think it should be an easy matter to pass to the $l_p$ spaces by taking limits.

I'm not sure what to do about the second inequality yet.

share|cite|improve this question
A suggestion for the first inequality: assume without loss off generality that $\|x\|_p = 1$ and use that for $p \leq q$ and $|t| \leq 1$ we have $|t|^q \leq |t|^p$. For the second inequality, you want to assume that $a$ only has $n$ non-zero entries, otherwise it is wrong. If you make this assumption, consider the sequence having $n$ entries $1$ and apply Hölder to a modification of $a$, as you suspected. – t.b. Jun 1 '12 at 9:37
Is there a way to use Hölder to get the first inequality, the one that shows the $p$ norm dominates the $q$ norm? – Potato Jun 1 '12 at 19:45
up vote 7 down vote accepted

For any $x,y\in\mathbb{R}^n,$ let us define $x\ast y=(x_iy_i)_{i=1,\ldots,n}\in\mathbb{R}^n.$ For any $p,q,r\in[1,\infty]$ such that $\frac{1}{p}+\frac{1}{q}=\frac{1}{r}$, we have a generalization of Hoelder inequality $$||x\ast y||_r\leq ||x||_p||y||_q\tag{*}.$$

By applying (*) taking $y=(1,\ldots,1),$ we get $$||x||_r\leq n^{\frac{1}{r}-\frac{1}{p}}||x||_p.$$

Edit About the first inequality $||x||_p\geq ||x||_q,\textrm{ when }1\leq p\leq q\leq\infty.$ Apart from the trivial case $q=\infty,$ a possible derivation is as follows $$||x||_p^q=\left(\Sigma_{i}|x_i|^p\right)^{q/p}\geq \Sigma_{i}|x_i|^q=||x||_q^q.$$

Here we have used the majoration $\left(\Sigma_{i}|x_i|^p\right)^{q/p}\geq \Sigma_{i}|x_i|^q$ which is justifed by the remark that, for any $\alpha\in [1,\infty[,$ the function $f(t)=(1+t)^\alpha- 1-t^\alpha$ is nonnegative.

share|cite|improve this answer
The generalization is obtained by using Hoelder inequality for the pair of conjugate exponents $(\frac{p}{r},\frac{q}{r}).$ – Giuseppe Jun 1 '12 at 10:22
Thank you! Very slick. – Potato Jun 1 '12 at 10:23
@Potato It is not possible because $p,q,r\in[1,\infty]$ and $\frac{1}{p}+\frac{1}{q}=\frac{1}{r},$ so $\frac{r}{p},$ $\frac{r}{q}$ are non-negative and their sum is $1$, consequently they have to belong to $[0,1].$ Now where are they reciprocals? in $[1,\infty].$ – Giuseppe Jun 1 '12 at 10:31
Do you see a way to use Hölder to prove the first inequality? I am curious if this is possible. – Potato Jun 1 '12 at 19:46
@Potato I don't know if it is possible, but I have reported an alternative derivation. – Giuseppe Jun 2 '12 at 17:29

Your Answer


By posting your answer, you agree to the privacy policy and terms of service.

Not the answer you're looking for? Browse other questions tagged or ask your own question.